Analytical evaluation of a new route pptimization scheme for nested mobile network - Hassan Abdalla Hashim, Aisha; Senan, Shayma; Khalifa, Othman Omran; Hameed, Shihab A.; Zeki, Akram M.; Daoud, Jamal Ibrahim (IDOSI Publication, 2013)
As the Internet becomes more and more accessible, claims for mobility are not limited anymore to single hosts. Supporting networks’ roaming that move as one entity is required in order to enable the transparency of Internet in mobile platforms, like cars, trains, planes, buses, etc. To accomplish this, NEMO Basic Support has been proposed and developed by the Internet Engineering Task Force (IETF) in order to provide an efficient communication. Nevertheless, NEMO still suffers from some limitations, especially in case of nested mobile network. This paper presents new route optimization scheme for nested mobile network using hierarchical structure with Binding Update Tree (BUT). This framework should reduce packet overhead, handoff latency, packet transmission delay and achieve optimal routing. Lastly, this paper will compare analytically between bi-directional tunnelling used by NEMO BS and route optimization of the proposed scheme.